Analysis of Risk Factors Associated with Survival COVID-19 Confirmed Patients - Eni Purwanty; Permata, Eva Nilam (RSUP Dr Moh Hoesin Palembang, 2023)
Background: COVID-19 is a pandemic that occurs in all parts of the world and can cause worsening health conditions and even death. Several factors are suspected to aggravate risk factors that can worse clinical conditions and cause death in COVID-19 patients. Risk factors such as age, gender, and the presence or absence of chronic disease are often associated with increased mortality in COVID-19 patients. This study aimed to determine the relationship between factors that affect the survival of COVID-19 patients, such as age, gender, diabetes mellitus, hypertension, heart disease, kidney disease, lung disease, smoking history, alcohol history, and obesity. Methods: An analytical description study of 66 participants was conducted for bivariate and multivariate analysis. Results: The results showed that aged more than 45 years(p=0,001; OR 6,111; 95% CI: 2.102-17.769), male (p=0,003; OR 5.417; 95% CI: 1.862-15.756), diabetes mellitus (p=0,000; OR 36.000; 95% CI: 7.194-180.151), heart disease (p=0,003; OR 9.286; 95% CI: 1.894-45.522), kidney disease (p=0,001; OR 8.953; 95% CI: 2.192-33.686) dan lung disease (p=0,002; OR 7.632; 95% CI: 1.943-29.971), smoker (p=0,003; OR 4.846; 95% CI: 1.683-13.955), dan obesity (p=0,005; OR 4.875; 95% CI: 1.600-14.855) influenced the patient's survival. Conclusion: Risk factors from age, gender, diabetes mellitus, heart disease, kidney disease, lung disease, smoking, alcoholism, and obesity influence the survival of confirmed COVID-19 patients. Among these factors, the most influential is diabetes mellitus.